Comparison of the Performance of Mini Generator Water Turbines in Series and Parallel Flow Systems - Kriswidijatmoko, Mikael Adi; Hariyanto, Rudi; Widiharsa, Fransiskus Asisi (TRANSMISI, 2023)
The need for electricity is crucial in modern life, but the depletion of fossil fuel resources and their negative impact on the environment has led to the need for alternative, sustainable, and renewable energy sources. One of the most widely used renewable energy sources is hydro energy, which can be harnessed through the use of water turbine generators. This research aims to design, prototype, and test the performance of a mini-series and parallel water turbine generator system with a 24-volt system. Furthermore, this research will evaluate the difference in performance between the series and parallel systems and analyze the efficiency of the mini-series and parallel water turbine generator system. The focus of this research is on the efficiency of the water turbine generator system with variations in water flow, but it does not cover large-scale industrial applications. This research aims to provide sustainable and environmentally friendly energy sources as an alternative to conventional energy sources. The results of this research can serve as a reference for researchers and practitioners interested in the development of renewable energy sources, particularly water turbine generators. In the testing, the Series Turbine Series Generator system with a water flow rate of 6.38 L/min produced a maximum power of 2.43 watts, while the Parallel Turbine Series Generator system with a water flow rate of 13.01 L/min produced a maximum power of 2.142 watts. The efficiency ratio between the Series Generator and Parallel Generator is 1.5, with the Series Generator achieving a maximum efficiency of 38.6% in the Series Turbine Series Generator system, and the Parallel Generator achieving a maximum efficiency of 25.3% in the Series Turbine Parallel Generator system.